PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN KEPERCAYAAN TERHADAP KEPUASAN PENUMPANG KERETA API ARGO MURIA JURUSAN SEMARANG TAWANG-GAMBIR(JAKARTA) (Studi pada Penumpang Kereta Api Argo Muria di Stasiun Semarang Tawang) - Avitrain Hali Wiedyani, 15.05.51.0231 (Students' Journal of Economic and Management, 2019)
The purpose of this study was to analyze the effect of service quality, price perception, and confidence in the satisfaction of passengers of the Argo Muria Railway in Semarang Tawang-Gambir (Jakarta) (Study on Argo Muria Train passengers at Semarang Tawang Station). The relationship of influence between variables is explained by using the method of multiple regression analysis. The results showed that, service quality has a positive and significant effect on customer satisfaction, price perception has a positive and significant effect on customer satisfaction and trust has a positive and significant effect on satisfaction of passengers of the Argo Muria Railway in Semarang Tawang-Gambir (Jakarta).